1999
DOI: 10.1111/j.1365-2621.1999.tb09856.x
|View full text |Cite
|
Sign up to set email alerts
|

Black Currant Nectar: Effect of Processing and Storage on Anthocyanin and Ascorbic Acid Content

Abstract: The degradation of anthocyanins and ascorbic acid in black currant nectar was studied during processing and storage. A continuous production process was used where the nectar was bottled within 4.0h; 20 % of both components were lost in the main stream process. The choice of enzyme mainly affected the recovery of ascorbic acid. Pasteurization resulted in a loss of 2-6 % of the ascorbic acid content. About 50% of the original content of monomeric anthocyanins remained after 6 months storage at 208C. The stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
53
1
9

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 19 publications
12
53
1
9
Order By: Relevance
“…This result was similar with Iversen (1999), who found minor loss of TAA in black currant after pasteurization. However, great losses of TAA were found in tomato juice (Dewanto et al, 2002), grapefruit juice (Igual et al, 2010) and fruit beverages (Cilla et al, 2012) during thermal treatments.…”
Section: Changes In Nutrition Qualities During Enzymatic Clarificatiosupporting
confidence: 81%
“…This result was similar with Iversen (1999), who found minor loss of TAA in black currant after pasteurization. However, great losses of TAA were found in tomato juice (Dewanto et al, 2002), grapefruit juice (Igual et al, 2010) and fruit beverages (Cilla et al, 2012) during thermal treatments.…”
Section: Changes In Nutrition Qualities During Enzymatic Clarificatiosupporting
confidence: 81%
“…Furthermore, the high amount of ascorbic acid in strawberry juice may have also contributed to the degradation of anthocyanins. The adverse effects of ascorbic acid on anthocyanins have been shown in strawberry juice Kertesz 1952, 1953;Meschter 1953), cranberry juice (Starr and Francis 1968), and black currant nectar (Iversen 1999). Contrary to strawberry juice, both sour cherry (Herrmann 1978) and pomegranate juices (Cemeroglu and others 1992) contain insignificant amounts of ascorbic acid.…”
Section: Degradation Kineticsmentioning
confidence: 99%
“…In blackcurrant juice, the increased anthocyanin concentration promotes also a higher colour stability (Giusti & Wrolstad 2003). Iversen (1999) reported that after 6-month storage of blackcurrant juice at 20°C, about 50% remained of the monomeric anthocyanins original content in blackcurrant nectar. The stabilities of delphinidins and cyanidins during storage were very similar.…”
Section: Methodsmentioning
confidence: 99%